Estimating Manpower Requirements. A Background Paper Prepared for the Graduate Medical Education Advisory Committee. Report No. 76-114 - Health Resources Administration (DHEW/PHS), Bethesda, MD. Bureau of Health Manpower; Health Resources Administration (DHEW/PHS), Bethesda, MD. Bureau of Health Manpower ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
This report on estimating physician manpower requirements is intended as a history and summary of the state of the art in manpower requirements estimation and forecasting. It describes the various ways in which manpower requirements have been estimated in recent years and discusses the variety of concepts, methods, definitions, and approaches that have been or can be used. It indicates some of the problems and limitations of current methods of estimating requirements and presents some existing requirements estimates for medical specialties. It also describes some of the needed improvements in data and methodology and offers some options for development of more adequate requirements estimates. Because the Graduate Medical Education Advisory Committee deals with ways of adjusting residency positions to meet the requirements for medical specialties in the coming years, the paper emphasizes projections of these requirements more than it does estimation of current requirements. (Author/JMF)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (Stock No. 241-186/1076).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Allied Health Occupations Education; Health Education; Health Occupations; Health Personnel; Health Services; Higher Education; Labor Needs; Labor Utilization; Medicine; Personnel Needs; Physicians; Prediction; Primary Health Care; Reports, Research